INCREASING THE CALCIUM SILICATE HYDRATE AMOUNT IN REACTIVE POWDER CONCRETE USING MARBLE POWDER - Widodo Kushartomo; Henny Wiyanto; Daniel Christianto (Spektra: Jurnal Fisika dan Aplikasinya)
This research aims to make ultra high strength Reactive Powder Concrete (RPC) with marble powder as one of the components. The use of marble powder can increase Calcium Silicate Hydrate (CSH) and the strength of RPC. The research method used to achieve the objectives is experimental and divided into two steps. The first step is the characterization of a marble and micro silica powder mixture. Stoichiometry calculations are performed to determine the composition of the mixture. The test sample is made in the form of pellets consisting of a mixture of marble powder, micro silica, and water. The water content used is at 30% - 50%. Maintenance is carried out by immersion in water with the temperature of 20oC for 27 days and in steam at temperatures 200oC, 250oC, and 300oC with 2 atm pressure for 4 hours. Material characterization is carried out using X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The second step in this research is the RPC compressive strength test. The test sample is made in the form of a cube measuring 50 x 50 x 50 mm. This cube is a mixture of water, cement, micro silica, marble powder, sand, and superplasticizer. Material composition is arranged based on the characterization of the sample pellet test, and maintenance of the sample cube test is carried out as in the sample pellet test.